Philosophical Foundations of Post-Non-Classical Ideas - NURULLIN, Rafail Asgatovich (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The goal of this study if to show the importance of humanist ideals in the modern civilization. In the world of global interconnectedness, human agency is becoming global as well. The main method employed in this study is dialectic which allows to speculatively construct any system using the language of universal categories. We also applied general scientific methods of the system theory, cybernetics, synergetics and philosophy of virtual reality. The study in general shows that all the main problems of an individual reside in the discrepancy between the level of spirituality in the society and the level of production and consumption of comforts of civilization. RESUMEN El objetivo de este estudio es mostrar la importancia de los ideales humanistas en la civilización moderna. En el mundo de la interconexión global, la agencia humana también se está volviendo global. El método principal empleado en este estudio es la dialéctica que permite construir especulativamente cualquier sistema utilizando el lenguaje de categorías universales. También aplicamos métodos científicos generales de la teoría de sistemas, cibernética, sinergética y filosofía de la realidad virtual. El estudio en general muestra que todos los problemas principales de un individuo residen en la discrepancia entre el nivel de espiritualidad en la sociedad y el nivel de producción y consumo de comodidades de la civilización.